Analisis Kinerja Keuangan dengan Metode Dupont System Pada Perusahaan PT. Air Minum Giri Menang (Perseroda) Periode 2020-2024 - Ni Putu Aryani Sintia Wijayanti; Ni Luh Putu Anom Pancawati; Armi Sulthon Fauzi (PT Maju Malaqbi Makkarana, 2026)
This study aims to analyze the financial performance of PT. Air Minum Giri Menang (Perseroda) using the DuPont System Method. This study uses a quantitative descriptive approach with secondary data in the form of financial statements for the 2020–2024 period obtained through literature and documentation studies. The research sample includes the statement of financial position and income statement. The indicators used consist of Net Profit Margin (NPM), Total Asset Turnover (TATO), Return on Investment (ROI), Equity Multiplier (EM) and Return on Equity (ROE). The results of the study indicate that the company has a fairly good ability to generate profits, as reflected in the average Net Profit Margin of 22.95% and is above the industry standard. However, asset utilization is still not optimal as indicated by the Total Asset Turnover value of 0.26 times, resulting in a low Return on Investment of 5.97%. The company's capital structure, indicated by the Equity Multiplier of 1.60 times, indicates that the company uses more equity than debt, so that financial risk is relatively low, but has not been able to optimize profit increases. This situation impacted the Return on Equity (ROE), which was only 9.57%, still below industry standards. Therefore, the low ROE is due to suboptimal asset utilization and capital structure, despite the company's relatively strong profit-generating ability.